Six species of bamboos, that were andong bamboo (Gigantochloa verticillata), tali bamboo (Gigantochloa apus), hitam bamboo (Gigantochloa nigrocillata), ampel bamboo (Bambusa vulgaris), betung bamboo (Dendrocalamus asper), and kuning bamboo (Bambusa vulgaris), were analyzed for their fiber morphological as well as their physical-chemical properties. Results of these analysis would be used as a matter of consideration in choosing species of bamboos to be used as raw material for pulp and paper. Fi - Widya FATRIASARI; Euis HERMIATI (Departemen Hasil Hutan, IPB, 2008)
Six species of bamboos, that were andong bamboo (Gigantochloa verticillata), tali bamboo (Gigantochloa apus), hitam bamboo (Gigantochloa nigrocillata), ampel bamboo (Bambusa vulgaris), betung bamboo (Dendrocalamus asper), and kuning bamboo (Bambusa vulgaris), were analyzed for their fiber morphological as well as their physical-chemical properties. Results of these analysis would be used as a matter of consideration in choosing species of bamboos to be used as raw material for pulp and paper. Fiber morphological analyses include determination of fiber dimensions and followed by calculation of derivation of fiber dimensions. Determination of fiber dimensions includes fiber length, fiber diameter, lumen diameter and cell wall thickness, while calculation of derivation fiber dimensions includes runkell ratio, felting power/slenderness), muhlsteph ratio, coefficient of rigidity and flexibility ratio. Physical analyses include moisture content and specific gravity, while chemical analyses include determination of extractive (ethanol-benzene), hot water solubles, cold water solubles, lignin, holocellulose, ash and silicate contents. Results of this study showed that of the six species of bamboos studied, kuning bamboo had the most suitable properties as raw material for pulp and paper, followed by betung, tali, andong, hitam, and ampel bamboos. Keywords : Bamboo, fiber morphology, physical-chemical properties, pulp, paper